نبی اکرم ﷺ کی سیرت میں انسانی نفسیات کی تربیت: جدید نفسیاتی تھیوریز کا اسلامی تجزیہ: PSYCHOLOGICAL TRAINING IN THE SEERAH OF PROPHET MUHAMMAD ﷺ: AN ISLAMIC ANALYSIS IN THE LIGHT OF MODERN PSYCHOLOGICAL THEORIES (Contemporary Journal of Social Science Review, 2025)
This article presents a comprehensive study of the psychological training of humans in the Seerah of Prophet Muhammad ﷺ and its correlation and critical analysis with modern psychological theories. The primary aim of the study is to demonstrate how the prophetic teachings provide practical, moral, and spiritual guidance for human personality, emotions, behaviors, and social relationships, and to examine their compatibility or divergence with modern psychological constructs such as personality development, emotional regulation, moral development, and social cohesion.The research analyzes the prophetic principles of psychological training in different groups youth, women, and social relationships based on the Quran and Sunnah. Furthermore, it compares these principles with modern psychological theories, including Freud’s Id, Ego, and Superego framework, B.F. Skinner’s behavioral reinforcement, and Jung’s concept of individuation. The study highlights that the holistic and spiritual nature of Islamic training provides a unique and comprehensive model for personality development and psychological resilience, which complements and sometimes extends beyond the scope of modern psychology.